Audience Reactions to Reporting of Floods in Malaysia: Flood Victims and Non-Flood Victims - Ning, Li; Su Hie, Ting (Penerbit UKM (UKM Press), 2025)
This study examines compares audience reactions of flood victims and non-flood victims to newspaper reporting of floods in Malaysia. The objectives of this study are: (1) to compare the affective, behavioural and cognitive themes in the narratives of flood victims and onlookers about flood incidents, and (2) to describe participants' views on the roles of newspapers vis-à-vis social media as sources of flood news. Semi-structured interviews were conducted with 20 participants (15 flood victims and (5 non-flood victims). For logistics convenience, the participants were selected from Kuching and Kota Samarahan in Sarawak, Malaysia. Analysis of the interviews using the Affective Behaviour-Cognitive (ABC) Model of Attitudes showed greater emotional engagement of flood victims with flood news compared to non-flood victims who were inclined towards cognitive responses. The flood victims had negative attitudes towards floods and blamed authorities for poor flood management. However, the non-flood victims’ emotional responses were balanced between gratefulness that they did not suffer floods and worry as the victims. The flood victims’ cognitive responses focused on economic, psychological and health effects of flooding while the non-flood victims rationalised that there was good government-citizen collaboration in flood management. Both groups hoped for personal stories in flood news but flood victims also wished for informative articles on flood warnings, safety measures and on-going flood mitigation initiatives. Regional newspapers were preferred as flood news sources compared to national newspapers but non-flood victims also enjoyed sharing social media updates on the floods. The study provides insights for newspapers to publish more engaging news articles on floods and enhancing its role to educate the public about flood mitigation.